Using browsers with hardware for embedded systems - Mulder, Patrick; Breseman, Kelsey (O'Reilly Media, Inc., 2016)
We think of web browsers as running on desktop or mobile devices, but browsers can also run on embedded hardware. This means we can use JavaScript and Node.js to control physical devices, such as for the Internet of Things. In this lesson, we'll set up a basic project structure, and then add some JavaScript and SVG for graphics. We'll then explore communicating with hardware through toggling state of digital inputs and outputs. Why is it important? Web browsers make excellent interfaces for hardware, because they come on every system, make serial communication convenient, and provide a screen, which many embedded systems often don't have on their own. Using the browser as the interface, JavaScript and Node.js provide communication between applications and hardware. What you'll learn--and how you can apply it Learn how to use web browsers as interfaces for embedded hardware and understand basic messaging between Node.js applications and hardware. This lesson is for you because ... You already have some experience with hardware and software and are interested in getting the two to talk to each other You want to be able to build prototypes of physical devices, leveraging the power of JavaScript Prerequisites Prior experience with JavaScript, Node.js, and microcontrollers (such as Arduino) Materials or downloads needed in advance None This lesson is taken from Node.js for Embedded Systems by Patrick Mulder and Kelsey Breseman.